(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2007)
The pattern and number of rugae in north Indian population and its change with ages was studied. Two hundred three (M: F 102:101, age between 18-26 years) dental castes were studied. There was significant increase in length of rugae found with age. Straight type rugae are common in north Indian population. This study will help in identifications of north Indian population.